The COVID-19 pandemic presents an opportunity to develop more sustainable health workforces - Bourgeault, Ivy L; Maier, Claudia B; Dieleman, Marjolein; Ball, Jane; MacKenzie, Adrian; Nancarrow, Susan; Nigenda, Gustavo; Sidat, Mohsin (Université d'Ottawa | University of Ottawa, 2020)
Abstract This commentary addresses the critically important role of health workers in their countries’ more immediate responses to COVID-19 outbreaks and provides policy recommendations for more sustainable health workforces. Paradoxically, pandemic response plans in country after country, often fail to explicitly address health workforce requirements and considerations. We recommend that policy and decision-makers at the facility, regional and country-levels need to: integrate explicit health workforce requirements in pandemic response plans, appropriate to its differentiated levels of care, for the short, medium and longer term; ensure safe working conditions with personal protective equipment (PPE) for all deployed health workers including sufficient training to ensure high hygienic and safety standards; recognise the importance of protecting and promoting the psychological health and safety of all health professionals, with a special focus on workers at the point of care; take an explicit gender and social equity lens, when addressing physical and psychological health and safety, recognising that the health workforce is largely made up of women, and that limited resources lead to priority setting and unequitable access to protection; take a whole of the health workforce approach—using the full skill sets of all health workers—across public health and clinical care roles—including those along the training and retirement pipeline—and ensure adequate supervisory structures and operating procedures are in place to ensure inclusive care of high quality; react with solidarity to support regions and countries requiring more surge capacity, especially those with weak health systems and more severe HRH shortages; and acknowledge the need for transparent, flexible and situational leadership styles building on a different set of management skills.